PERAN LPDB DAN KUMKM NATUNA UNTUK MENJADI POROS MARITIM INDONESIA - REZZY EKO CARAKA (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2019)
This research was motivated by Nusantara Jaya Expedition activities which were followed by Researcher and organized by the Coordinating Ministry of Maritime Affairs of the Republic of Indonesia in Natuna. The abundant natural resources in Natuna are mainly marine wealth and fisheries, which are then targeted by the Indonesian government as Indonesia's maritime axis so that more in-depth analysis. The purpose of this study is to find out which areas have similar closeness and will make it easier for LPDB to map potential areas in Natuna. This study involved three dependent variables consisting of GRDP, UN, and Number of Fisheries Households. Then it meant 12 independent variables comprising Capita Expenditures, Poverty Index, Population, Micro Business Number, Total Business, Number of Traders, Number of Cooperatives, Production, Number of Aquaculture Households, Motorless Boats, Outboard Motorboats, and Motorboats. All analysis objectives can be answered using the principal component analysis biplot. Biplot is a method to make images in many dimensions of space into images in two-dimensional areas. The first Biplot obtained 77.28 percent of the total diversity of actual data. The interpretation of the main component of the biplot produced can explain very well the relationship between the rate of GDP in Natuna District to capita expenditure and the poverty depth index and the Gini ratio in Natuna. In the second Biplot obtain 82.17 percent of the total diversity, which means that it was able to explain 82.17 percent of the United Nations Against Population, Number of Micro Businesses, Total Businesses, Traders, Number of Cooperatives. In this analysis also found four dimensions of regions that have similar relationships, making it easier for LPDB to map the potential of the area in Natuna as Indonesia's maritime.